A Decision-Making Framework for Subcontractor Selection in Construction Projects. Issue 2 (3rd April 2018) - Abbasianjahromi, Hamidreza; Sepehri, Mehran; Abbasi, Omid
Abstract: Subcontractor (SC) selection is a critical part of SC management, and a major challenge is the existence of multiple criteria that the project management team needs to evaluate in the selection process. To overcome this challenge, the Kano model is applied to classify the selection criteria into five categories including must-be, reverse, one-dimensional, attractive, and indifferent. Data were obtained via a questionnaire based on Kano model concepts to categorize the identified selection criteria. The obtained results show that the selection criteria can be categorized into three categories; must-be, one-dimensional, and attractive. According to this categorization, the weight of criteria is extracted by applying the Analytic Hierarchy Process. Then, a fuzzy multi-attribute decision framework is developed to select the best SC with two main components, screening by the must-be criteria category and selection based on the one-dimensional and attractive criteria categories. A case example of the framework application and the results of a questionnaire are presented and validate acceptance of the framework accuracy.